Thermal characterisation analysis and modelling techniques for CubeSat-sized spacecrafts. (17th October 2017) - Ali, Anwar; Ullah, Khalil; Rehman, Hafeez Ur; Bari, Inam; Reyneri, Leonardo M.
ABSTRACT: Recently, universities and Small and Medium Enterprises (SMEs) have initiated the development of nanosatellites because of their low cost, small size and short development time. The challenging aspects for these satellites are their small surface area for heat dissipation due to their limited size. There is not enough space for mounting radiators for heat dissipation. As a result, thermal modelling becomes a very important element in designing a small satellite. The paper presents detailed and simplified generic thermal models for CubeSat panels and also for the complete satellite. The detailed model takes all thermal resistances associated with the respective layers into account, while in the simplified model, the layers with similar materials have been combined and are represented by a single thermal resistance. The proposed models are then applied to a CubeSat standard nanosatellite called AraMiS-C1, developed at Politecnico di Torino, Italy. Thermal resistance measured through both models is compared, and the results are similar. The absorbed power and the corresponding temperature differences between different points of the single panel and complete satellite are measured. In order to verify the theoretical results, thermal resistance of the AraMiS-C1 and its panels are measured through experimental set-ups. Theoretical and measured values are in close agreement.